PENGARUH HARGA, PROMOSI PENJUALAN DAN KUALITAS PELAYANANG TERHADAP MINAT BERMAIN ULANG DI TRANS STUDIO MINI SETIABUDI SEMARANG MELALUI KEPUASAN PENGUNJUNG SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Pengunjung Trans Studio Mini Setiabudi Semarang di Kota Semarang dan Sekitarnya) - Renata, Tasya Rizky; Prabawani, Bulan (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2018)
Trans Studio Mini is one of indoor theme park located in Semarang that managed to attract people since their official openings on June 2017, but in the end of 2017 to the middle of 2018 visitors of Trans Studio Mini Setiabudi Semarang keep decresing. This study aims to determine the influence of price, sales promotion and service quality towards interests of re-visit through the visitors satisfaction of Trans Studio Mini Setiabudi Semarang. Type of research used is explanatory research. The sampling technique used purposive sampling method. The number of samples taken as many as 100 respondents. The data analysis technique used is cross tabulation test, correlation test, determination test, simple linear regression test, multiple linear regression test, t test, F test, sobel test with the help of IBM SPSS (Statistical Product and Service Solution) program version 16.0.Â The results showed that variable of visitor satisfaction is partial mediation variable which able to mediate influence of price and service quality to repeat interest because output of the test sobel is bigger than t table, but variable of visitor satisfaction is not partial mediation variable which able to mediate promotion effect sales of interest to re-playing because output of the test sobel is s smaller than t table. Suggestion that can be afford in this research is that the company should understand vistorsâ€™s expectations more. Especially on the price, sales promotion and service quality to increase visitors satisfaction and interests of re-visit.